The Impact of Islamic Service Quality, Complaint Handling, and Margins on Customer Satisfaction in Islamic Financial Institutions: Pengaruh Kualitas Layanan Syariah, Penanganan Keluhan, dan Margin terhadap Kepuasan Nasabah di Lembaga Keuangan Syariah - Nasrulloh, Nasrulloh; Saputri, Nensy Dwi (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2024)
Abstract: The increasing competition within the financial industry has compelled Islamic Financial Institutions to prioritize customer satisfaction as a primary objective. This study aims to analyze the influence of Islamic service quality, complaint handling, and margins on customer satisfaction using a mixed-method approach with a sequential explanatory design. In the quantitative phase, a survey was conducted with 85 customers selected randomly using a simple random sampling technique, where data were collected through a 5-point Likert scale questionnaire and analyzed using multiple linear regression in SPSS version 25. The qualitative phase involved semi-structured interviews with 10 customers selected through purposive sampling, analyzed thematically based on social capital theory. The results indicate that Islamic service quality, complaint handling, and margins positively and significantly influence customer satisfaction, contributing to 72.2% of the variability in customer satisfaction. The qualitative analysis confirms that trust, Islamic norms, and social networks play a pivotal role in enhancing customer satisfaction, particularly through transparent, responsive, and fair Islamic service delivery. This study recommends improving empathetic service delivery, prompt complaint resolution, and competitive yet Sharia-compliant margin adjustments to enhance the competitiveness of Islamic financial institutions. The theoretical implication highlights the importance of social capital as a key element in fostering sustainable relationships between Islamic financial institutions and their customers. Abstrak: Peningkatan persaingan dalam industri keuangan mendorong Lembaga Keuangan Syariah untuk memprioritaskan kepuasan nasabah sebagai tujuan utama. Penelitian ini bertujuan untuk menganalisis pengaruh kualitas pelayanan Islami, penanganan komplain, dan margin terhadap kepuasan nasabah menggunakan metode mixed method dengan desain eksplanatori sekuensial. Pada tahap kuantitatif, survei dilakukan terhadap 85 nasabah yang dipilih secara acak menggunakan teknik random sampling, yang mana data dikumpulkan melalui kuesioner skala Likert 5 dan dianalisis menggunakan regresi linear berganda dengan SPSS versi 25. Tahap kualitatif melibatkan wawancara semi-terstruktur dengan 10 nasabah yang dipilih secara purposive sampling, dengan analisis tematik berdasarkan teori modal sosial. Hasil penelitian menunjukkan bahwa kualitas pelayanan Islami, penanganan komplain, dan margin memiliki pengaruh positif dan signifikan terhadap kepuasan nasabah, dengan kontribusi sebesar 72,2% terhadap variabilitas kepuasan nasabah. Analisis kualitatif menegaskan bahwa kepercayaan, norma Islami, dan jaringan sosial memainkan peran penting dalam meningkatkan kepuasan nasabah, terutama melalui pelayanan Islami yang transparan, responsif, dan adil. Penelitian ini merekomendasikan peningkatan layanan berbasis empati, penyelesaian komplain secara cepat, dan penyesuaian margin yang kompetitif namun sesuai syariah untuk meningkatkan daya saing lembaga keuangan syariah. Implikasi teoretis menyoroti pentingnya modal sosial sebagai elemen kunci dalam membangun hubungan berkelanjutan antara lembaga keuangan syariah dan nasabah.